Managing reality managing change - Mitchell, Bronwyn (Institution of Civil Engineers (ICE), 2005)
Managing Reality Book 4 Managing Change is for those who are managing change under the contract; whether for the employer or the contractor (or subcontractor) the management of change is often a major challenge whatever the form of contract. The ECC deals with change in a different way to traditional forms. This book sets out the steps to efficiently and effectively manage change, bridging the gap between theory and practice.